THE KAMENNOE GOLD SULFIDE DEPOSIT (NORTHERN TRANSBAIKALIA, RUSSIA) AS A REPRESENTATIVE OF THE RIPHEAN EPITHERMAL GOLD-TELLURIDE-SILVER ORE MINERALIZATION - Mironov A.G.; Damdinov B.B.; Guntypov B.B.; Zhmodik S.M.; Borovikov A.A.; Verkhovtseva N.V. (My University, 2004)
The Kamennoe gold sulfide deposit, situated in Riphean volcanogenic-sedimentary deposits of the Yakornaya suite (island arc complex) in Northern Transbaikal region, was studied. Unlike many gold quartz vein deposits and occurrences of the Muisk metallogenic zone, the Kamennoe deposit is characterized by the Au-Te-Ag mineralization type, a subordinate role of quartz, an abundance of carbonates in massive and impregnated sulfide ores, and quartz-sericite wallrock alteration. Thermobarometric and chemical studies of ores showed an ore deposition interval of 180-80°C. This, in line with such mineral assemblages as the hessitepetzite, etc., testifies to an epithermal ore mineralization of the deposit. The following ore types were distinguished: quartz-carbonate-pyrite, pyrite-sphalerite-chalcopyrite, and chalcopyrite-fahlore, formed in three stages. From earlier to later stages, the ores show an increase in Ag, Sb, and Hg contents, whereas Mn content increases (up to 24 wt %) in carbonates. Gold occurs as microadmixtures in sulfides or, rarely, in the free state with the fineness from 920 to 58‰. Pb, Au, and Ag tellurides are abundant. Such rare minerals as coloradoite, kervellite, tellurcanfieldite, tellurantimonite, etc., were identified. In line with other evidence, hydrothermally altered rocks dated at 563 ± 60 Ma (Rb-Sr) allow us to attribute the formation of the mineralization to an island arc volcanism of the Baikal-Muisk volcanic belt. According to S, C, and Sr isotope characteristics, sources of the ore substance might have been deep-seated, and the massive sulfide mineralization was formed in submarine conditions or back arc troughs of the Kuroko type.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей